A new endophytic fungus, Tulasnella phuhinrongklaensis (Cantharellales, Basidiomycota) isolated from roots of the terrestrial orchid, Phalaenopsis pulcherrima - Rachanarin, Chanalug; Suwannarach, Nakarin; Kumla, Jaturong; Srimuang, Kanok-Orn; Mckenzie, Eric H.c.; Lumyong, Saisamorn (Phytotaxa, 2018)
A new species of endophytic fungus, described herein as Tulasnella phuhinrongklaensis, was isolated from a root of a terrestrial orchid, Phalaenopsis pulcherrima, in Phitsanulok Province, Thailand. This species is characterized by its cream to white colonies, branched chains of spherical to ellipsoid monilioid cells and absence of sclerotia. The uniqueness of the species was confirmed by a phylogenetic analysis of combined sequences of internal transcribed spacer (ITS) and large subunit region (LSU) of ribosomal DNA, and a nucleotide divergence of the ITS sequences. The phylogenetic result showed that T. phuhinrongklaensis formed a monophyletic lineage clearly distinct from other Tulasnella and Epulorhiza species, the asexual morph of Tulasnella. The nucleotide divergence of ITS sequences in the new fungus ranged from 50.66–57.93% in genera Tulasnella and Epulorhiza. A description and illustrations of the new species are provided.